Maracatu : faces e interfaces de uma experiência religiosa - Prazeres, George Demetrio Alves dos (2007)
Our work has for objective to describe one of the religious aspects of the man afro-brazilian and one of its forms of resistance, in the search of the reconstruction and preservation of the basic values for its existence. Maracatu is, the principle, an attempt of restoration, in strange land, of dynasties wasted for the system of slavery, having had its origin and its apogee in the doors of the churches, with its brotherhoods. Maracatu appears in our state, still in the colonial period, as form of resistance and maintenance of the religion of the man afrodescendant. The objective of this work is to analyze maracatu as a "niche" of interpretation and preservation of the cultural values afro-brazilians who, in its symbolic constellation makes a religious experience in which the basic elements of the ethos African is reinterpretado, celebrated and socialized between the involved people